Perancangan dan Implementasi Website UMKM Semangat Muda Terintegrasi WhatsApp AI Chat untuk Meningkatkan Penjualan Produk - Nur Aswan Multazam; Yusi Gunawan; Mesra Betty Yel (AJAD : Jurnal Pengabdian kepada Masyarakat, 2026)
This community service program designed a digital solution for SM Cloth "Semangat Muda", an MSME in Tegal providing screen-printing and printing services. Two core problems were identified: promotional channels that remain narrow, and the recurring risk of lost orders caused by delayed manual responses during the ordering process. The proposed solution consists of an MSME website serving as a product catalog and service information medium, paired with a WhatsApp AI Chat system designed to answer customer queries and collect order details in a structured manner. Development follows the Waterfall SDLC model, beginning with a needs assessment through direct observation and interviews, followed by UI/UX design, relational database design, and chatbot conversation flow design with service orchestration. Outputs include a modular website design covering catalog, service information, and WhatsApp-based ordering, as well as a chatbot design with conversation context storage and order logging. The proposed system is expected to reduce response time, broaden digital promotional reach, and reinforce the business image of the MSME.